Macroeconomic Determinants of Stock Price Changes: Empirical Evidence From Nigeria - Inegbedion, Henry Egbezien (Indian Journal of Finance, 2012)
The study examined the Macroeconomic Determinants of Stock Price Behavior in the Nigerian stock market. The objective was to determine whether selected macroeconomic variables, interest rate, inflation rate, and exchange rate affect stock price movements. Unit root test was conducted to test for Stationarity as well as to determine the degree of integration. Research data were analyzed first, by using the Ordinary least Squares Method. However, with a calculated Durbin-Watson Statistic of 0.20665, it was evident that the stochastic error terms were auto correlated, thus indicating that the results of the Ordinary least square test are spurious. This necessitated some adjustment to correct the presence of the auto correlation of the stochastic error terms; this was done using Cochran-Orcutt autoregressive model of order 2 AR (2). The results of the study showed that some macroeconomic variables significantly affect stock price movements and thus affect the stability of the Nigerian Capital Market.